2006
DOI: 10.2323/jgam.52.9
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid substitutions in malate dehydrogenases of piezophilic bacteria isolated from intestinal contents of deep-sea fishes retrieved from the abyssal zone

Abstract: IntroductionIn a previous paper (Saito and Nakayama, 2004), to elucidate the molecular basis for malate dehydrogenase (MDH) functions at high pressure and low temperature, we cloned, sequenced, and overexpressed the gene encoding MDH from the obligately piezophilic deep-sea bacterium Moritella sp. strain 2D2 isolated Key Words--amino acid substitutions; Coryphaenoides yaquinae; deep-sea piezophilic bacteria; intestinal contents of deep-sea fishes; malate dehydrogenase (MDH); Moritella sp.; Shewanella sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…strain HTA-462 (Shirai et al 2008), Cu/Zn superoxide dismutase from the deep-sea yeast Cryptococcus liquefaciens strain N6 (Teh et al 2008), and superoxide dismutase from the deep-sea worm Alvinella pompejana (Shin et al 2009), as found for other hyperthermophilic enzymes (Vieille and Zeikus 2001). Deep-sea enzymes with unknown crystal structures generally have the same folded structures as their normal homologs in homology modeling (Purcarea et al 1997;Saito et al 2006;Kato et al 2008b;Brindley et al 2008;Xie et al 2009). Taken together, these results indicate that the tertiary structures of deep-sea enzymes are essentially the same as those of their homologs from bacteria living in ambient atmospheric pressure environments.…”
Section: Primary and Tertiary Structures Of Deep-sea Dhfrsmentioning
confidence: 97%
“…strain HTA-462 (Shirai et al 2008), Cu/Zn superoxide dismutase from the deep-sea yeast Cryptococcus liquefaciens strain N6 (Teh et al 2008), and superoxide dismutase from the deep-sea worm Alvinella pompejana (Shin et al 2009), as found for other hyperthermophilic enzymes (Vieille and Zeikus 2001). Deep-sea enzymes with unknown crystal structures generally have the same folded structures as their normal homologs in homology modeling (Purcarea et al 1997;Saito et al 2006;Kato et al 2008b;Brindley et al 2008;Xie et al 2009). Taken together, these results indicate that the tertiary structures of deep-sea enzymes are essentially the same as those of their homologs from bacteria living in ambient atmospheric pressure environments.…”
Section: Primary and Tertiary Structures Of Deep-sea Dhfrsmentioning
confidence: 97%
“…21.5b, the backbone structure of this enzyme (PDB ID: 3vmk) completely overlaps with that of the normal homolog from S. oneidensis strain MR-1 (PDB ID: 3vmj) , which was collected from Oneida Lake (Venkateswaran et al 1999). The sequence length, level of identity with ecDHFR, and accession numbers for the DDBJ/GenBank/EMBL sequence databases are also indicated at the end of each sequence generally have the same folded structures as their normal homologs in homology modeling (Purcarea et al 1997;Saito et al 2006;Kato et al 2008b;Brindley et al 2008;Xie et al 2009). strain HTA-462 (Shirai et al 2008), Cu/Zn superoxide dismutase from the deep-sea yeast Cryptococcus liquefaciens strain N6 (Teh et al 2008), and superoxide dismutase from the deep-sea worm Alvinella pompejana (Shin et al 2009), as found for other hyperthermophilic enzymes (Vieille and Zeikus 2001).…”
Section: Primary and Tertiary Structures Of Deep-sea Dhfrsmentioning
confidence: 99%
“…In recent years analyses of protein structural and kinetic adaptations to high‐pressure deep‐sea environments has increased. This includes work on actin, bacterial tubulin (FtsZ), RNA polymerase, single‐stranded DNA binding protein, proteases, isopropylmalate dehydrogenases, malate dehydrogenase, and dihydrofolate reductase 36–42 …”
mentioning
confidence: 99%